2020
DOI: 10.1093/jisesa/ieaa119
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Characters for the Separation of Two Culex Species (Diptera: Culicidae) Based on Material From the Upper Midwest

Abstract: Mosquitoes (Diptera: Culicidae) in the Culex pipiens complex play a key role in the transmission and therefore epidemiology of a number of human and animal pathogens globally. These mosquitoes, and sympatric species of the genus Culex Linnaeus that are not within the Cx. pipiens complex, are often considered ‘impossible’ to distinguish by morphology in the adult female stage. In the United States, this is particularly true for Culex pipiens s.l. and Culex restuans Theobald, both of which are competent vectors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…infirmatus may again reflect broad occurrence across landscape types. In addition, the potential for unmeasured covariance between spatial and temporal niche dynamics, especially given these taxa are known to be tied to the dynamics of wet season timing in North and Central Florida, may contribute to observed patterns [ 53 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…infirmatus may again reflect broad occurrence across landscape types. In addition, the potential for unmeasured covariance between spatial and temporal niche dynamics, especially given these taxa are known to be tied to the dynamics of wet season timing in North and Central Florida, may contribute to observed patterns [ 53 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Culex spp. mosquitoes from gravid traps were stored at –20 °C, then identified to species based on morphological characters as part of a concurrent study (Ferreira-de-freitas et al 2020); some of these specimens were reported in that paper (C1 is labeled as “All Saints Cemetery”). Pools of approximately 50 Cx.…”
Section: Methodsmentioning
confidence: 99%
“…Trapping sites (gravid or NJLT) with less than three years of mosquito data were excluded from the study. All mosquito samples were identified using morphological keys (40, 82) where possible. Due to damage to morphological features that help to define Culex species (83), mosquito identifications of Culex pipiens and Culex restuans from NJLT traps were defined as Culex pipiens group as previously (32, 34).…”
Section: Methodsmentioning
confidence: 99%
“…Due to damage to morphological features that help to define Culex species (83), mosquito identifications of Culex pipiens and Culex restuans from NJLT traps were defined as Culex pipiens group as previously (32, 34). Gravid trap specimens were identified to species ( Culex pipiens ) (82). To normalize trapping efforts, raw mosquito counts were converted to a trap index (defined as the number of mosquitoes collected / number of trapping nights) and then averaged by week.…”
Section: Methodsmentioning
confidence: 99%